KONSEP KEPEMILIKAN DAN DISTRIBUSI DALAM EKONOMI ISLAM - Nuri Aslami; Sri Sudiarti (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Since the time of the Prophet, the issue of ownership has existed and resurfaced. However, the meaning of the phrase, also known as "Al-Milkiyyah," shifted at this time, from property, which was initially only utilized for the requirements of life, to power and power. Islamic economics aspires to create a fair distribution of income and riches in people's lives. This article aims to examine from an Islamic perspective the concept of ownership and distribution of wealth for human welfare. Because humans born on earth do not have anything. This research method uses qualitative methods with library research data analysis techniques. The results and discussion in this study include that property - according to Islam - is not private property (capitalism) nor is it shared property (socialism) but belongs to Allah, this is mentioned in the Qur'an and Sunnah. Allah SWT gives power to humans to own and use these assets. In Islam, it is stated that ownership has three types, namely individual, public, and state ownership. In terms of the object's context, ownership is divided into two, namely: Al Milk At Tamm (Perfect Ownership) and Al Milk An Naqish (Imperfect Ownership). The concept of distribution of wealth offered by Islamic economics in this case, among others, by creating an economic balance in society. Islamic economics offers priority steps that need to be taken by the competent authority which in this case is the government, namely: (1) Zakat; (2) The state must regulate the equal distribution of natural resources; (3) The wealth of the community must be managed by the state in the context of optimizing maximum results; (4) Community services that generate profits must be managed; and (5) non-profitable public services must be subsidized by the state. Keyword : Ownership, Distribution , Islamic Economy